2008
DOI: 10.2337/dc07-1525
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Glucagon-Like Peptide 1 and Inflammation Markers Among Severely Obese Adolescents

Abstract: OBJECTIVE -Compared with Caucasians, obese African-American adolescents have a higher risk for type 2 diabetes. Subclinical inflammation and reduced glucagon-like peptide 1 (GLP-1) concentration are linked to the pathogenesis of the disease. We determined the relationship between insulin resistance, ␤-cell activity, and subclinical inflammation with GLP-1 concentrations and whether racial disparities in GLP-1 response were present in 49 obese adolescents (14 Ϯ 3 years; 76% African American; 71% female). RESEAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In addition, the differences we have established in levels and relationships of some of these biomarkers, at least in relation to other populations (40,(43)(44)(45)(46) make our observations unique as a contribution to establishing a solid evidence base for the use of these markers in the prediction of cardiovascular disease risk in different populations. In addition, the differences we have established in levels and relationships of some of these biomarkers, at least in relation to other populations (40,(43)(44)(45)(46) make our observations unique as a contribution to establishing a solid evidence base for the use of these markers in the prediction of cardiovascular disease risk in different populations.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the differences we have established in levels and relationships of some of these biomarkers, at least in relation to other populations (40,(43)(44)(45)(46) make our observations unique as a contribution to establishing a solid evidence base for the use of these markers in the prediction of cardiovascular disease risk in different populations. In addition, the differences we have established in levels and relationships of some of these biomarkers, at least in relation to other populations (40,(43)(44)(45)(46) make our observations unique as a contribution to establishing a solid evidence base for the use of these markers in the prediction of cardiovascular disease risk in different populations.…”
Section: Discussionmentioning
confidence: 96%
“…In terms of obesity, physiological (e.g., inflammation, insulin resistance) 32,33 and health behavioral factors (e.g., poor dietary and exercise habits) 34 reportedly account for some of the observed racial/ethnic differences. Further, studies suggest that stress, in combination with health behaviors and obesogenic environments, explain both the higher prevalence of obesity and the lower prevalence of mental disorders, such as depression, among African Americans compared with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…who found that among severely obese adolescents, AA had lower GLP-1 responses to oral glucose (17). Importantly, our results extend these findings to demonstrate for the first time that ethnic differences in GLP-1 are also present in healthy children with normal body weight and normal glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few investigations have quantified incretin responses in AA and EA. Obese AA adults were found to have significantly higher fasting and postchallenge GLP-1 concentrations than EA adults (16), however, recent findings in obese adolescents seem to contradict these findings (17). …”
Section: Introductionmentioning
confidence: 96%